PATIENT SATISFACTION MEDIATES THE INFLUENCE OF HEALTH SERVICES QUALITY AND BRAND IMAGE ON PATIENT LOYALTY - Aily; Melitina Tecoalu; Wani Gunardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research has the intention to see the influence of health service quality and and brand image on patient loyalty which is mediated by patient satisfaction. The respondents of this study were the patients at RS Murni Teguh Sudirman Hospital. The testing of the hypothesis was conducted using quantitative research method with the total sample of 100 patients. Data with college questionnaireare to the respondents. The analysis technique that was used was the Partial Least Square - Structural Equation Modeling (PLS-SEM) from the SmartPLS program. Based on the analyzed data, it was found that there was an influence of health service quality and brand image on patient loyalty, mediated by patient satisfaction. Based on research results, it was found that there is an influence of the quality of health service on patient satisfaction. The quality of health service does not have a direct effect on patient loyalty. Brand image has a positive effect on patient satisfaction. Brand Image has a positive effect on client loyalty. Patient satisfaction positive effect patient loyalty. Health service quality has a positive effect on patient loyalty which is mediated by patient satisfaction. Brand image has a positive influence on patient loyalty which is mediated by patient satisfaction. The hospital has provided health services and a good image at RS Murni Teguh Sudirman so increasing patient satisfaction which ultimately increases patient loyalty.